2022
DOI: 10.1002/cche.10553
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry of wheat gluten proteins: Quantitative composition

Abstract: Background and Objectives: Wheat is essential to secure nutrition for the world's population. Its unique processing properties are largely determined by gluten protein content and composition.Findings: Gluten proteins are subdivided into gluten protein types, α-, γ-, ω1,2-, and ω5-gliadins and high-molecular-weight glutenin subunits and lowmolecular-weight glutenin subunits. The overall content and relative proportions of these types vary considerably depending on different genetic and environmental factors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 93 publications
0
29
0
Order By: Relevance
“…Wheat varieties were more numerous in the past; bread wheat landraces have been replaced by monocultures of pure genotypes, resulting in a loss of genetic diversity . It was found that the high-yielding modern varieties have a lower protein content and decreased proportions of gliadins but an increase in glutenins. , The gliadin/glutenin proportion similarly varies by wheat species: while glutenin is the dominant fraction in common wheat, gliadin makes up the highest fraction in species of so-called ancient wheats (einkorn, emmer, and spelt) as well as having an overall higher protein content. , Environmental conditions such as soil, temperature, and irrigation also play a role in protein composition . In parallel to a decrease in overall protein content in modern bread wheat, the starch content has increased .…”
Section: Discussionmentioning
confidence: 99%
“…Wheat varieties were more numerous in the past; bread wheat landraces have been replaced by monocultures of pure genotypes, resulting in a loss of genetic diversity . It was found that the high-yielding modern varieties have a lower protein content and decreased proportions of gliadins but an increase in glutenins. , The gliadin/glutenin proportion similarly varies by wheat species: while glutenin is the dominant fraction in common wheat, gliadin makes up the highest fraction in species of so-called ancient wheats (einkorn, emmer, and spelt) as well as having an overall higher protein content. , Environmental conditions such as soil, temperature, and irrigation also play a role in protein composition . In parallel to a decrease in overall protein content in modern bread wheat, the starch content has increased .…”
Section: Discussionmentioning
confidence: 99%
“…Rye quality assessment for baking includes proteins, fibers, and starches. In breadmaking, protein and specifically glutens are important in the binding and stretching of dough and improve bread moisture, rising, and crumb texture (Wieser et al., 2023). In contrast to wheat grain, which contains 8%–15% protein, of which 90% is gluten (Wieser et al., 2023), rye grains contain 3.5% gluten, contributing to a denser texture and higher moisture of rye bread (Deleu et al., 2020; Meeus et al., 2021; Schalk et al., 2017).…”
Section: Nutritional and Quality Components Of Ryementioning
confidence: 99%
“…In breadmaking, protein and specifically glutens are important in the binding and stretching of dough and improve bread moisture, rising, and crumb texture (Wieser et al., 2023). In contrast to wheat grain, which contains 8%–15% protein, of which 90% is gluten (Wieser et al., 2023), rye grains contain 3.5% gluten, contributing to a denser texture and higher moisture of rye bread (Deleu et al., 2020; Meeus et al., 2021; Schalk et al., 2017). Because of the lower gluten content, rye flour can be deglutenized (Walter et al., 2015), and rye flour components contribute to gluten‐free products (Mansberger et al., 2014).…”
Section: Nutritional and Quality Components Of Ryementioning
confidence: 99%
“…The success of wheat is largely due to the special chemical and physical properties of its gluten proteins that make up the essence of wheat uniqueness. They correspond to the storage proteins of wheat and represent around 70%–80% of total grain proteins (P. Shewry, 2019; Wieser et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In this review, we provide an updated and detailed insight into the chemistry of wheat gluten proteins with a focus on the qualitative composition. Different factors determining the quantitative composition of gluten are available in the associated review by Wieser et al (2022).…”
Section: Introductionmentioning
confidence: 99%